Analisis Kinerja Keuangan Pada PT. Blue Bird Tbk Sebelum Dan Setelah Pandemi - ulum, Bahrul; Nichayah, Galuh; Faizah, Riris Amirotul; Fitriana, Debby Gita (CV. ITTC INDONESIA, 2023)
The Covid-19 outbreak in Indonesia has had a huge impact on various sectors including the economy and finance. One of the sectors affected is the transportation sector and the object of research, namely PT. Blue Bird Tbk. This study analyzes the financial performance of PT. Blue Bird Tbk is based on ratios consisting of the influence of profitability ratios (ROA, ROE), liquidity ratios (CR), solvency ratios (DAR) and activity ratios (TATO) to profits (Y). The research method used is descriptive research with a quantitative approach. The results of the study show that the financial situation of PT Blue Bird Tbk is currently in an unfavorable phase due to the presence of new competitors. Followed by the worst financial conditions in 2020 due to government regulations which harmed the company's sales and revenue. In 2021 this is a breath of fresh air for PT Blue Bird Tbk to continue to increase its sales. And based on the results of the analysis that we did, we estimate that in the absence of a pandemic condition and the absence of government regulations, PT Blue Bird Tbk's economy will continue to improve.